Penerapan Teknologi Reproduksi Sapi Potong pada Peternakan Rakyat Kelompok Tani Makmur Sejahtera: Implementation of Reproductive Technology in Beef Cattle Farming at the Makmur Sejahtera Farmers' Group - Hasrin, Hasrin; Zulkharnaim, Zulkharnaim; Hasman, Hasman; Syamsuddin, Syamsuddin; Wulandari, Sri Helda; Sari, Anggun Permata; Nurhidayah, Asmaul Fitriana; Walinono, Andi Muh. Fuad Al Kautsar; Diansyah, Athhar Manabi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
One of the efforts to increase the calving rate in cattle is by applying artificial insemination guns. The main issue currently faced by the partners is the lack of implementation of artificial insemination guns and veterinary personnel, resulting in a low birth rate. The methods used in this community service program include focus group discussions and training on artificial insemination technology, animal health management, as well as livestock fattening, and feed processing based on local raw materials for pregnant cows. The outcome of this activity is reflected in the increased knowledge of the